The Relationship Between Maternal Knowledge and the Incidence of Hypertension in Pregnancy at Bhakti Medicare Hospital, Sukabumi - Octafiana, Dian Fitria; Novryanthi, Dhinny; Andriani, Ria (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Hypertension in pregnancy is a major cause of maternal and fetal morbidity and mortality, contributing to 14% of global maternal deaths. In Indonesia, it is the second leading cause of maternal mortality. Knowledge is an important determinant of health behavior, yet its link to pregnancy-induced hypertension remains underexplored in Sukabumi. Objective: To analyze the relationship between pregnant women’s knowledge and the incidence of hypertension in pregnancy. Methods: A quantitative cross-sectional study was conducted with 44 pregnant women diagnosed with hypertension in the Amarylis Room, Bhakti Medicare Hospital, Sukabumi (November–December 2024). Data were collected using a validated 15-item questionnaire. Knowledge level (good, sufficient, poor) and hypertension severity (mild, severe) were analyzed with the chi-square test (p < 0.05). Results: Most respondents had poor knowledge (45.5%) and severe hypertension (52.3%). Chi-square analysis showed a significant relationship between knowledge and hypertension incidence (p = 0.002). Severe hypertension was more frequent among women with poor knowledge (36.4%) compared to those with good knowledge (2.3%). Conclusion: Maternal knowledge significantly influences the incidence of hypertension in pregnancy. Educational interventions are urgently needed to reduce risks and improve maternal health outcomes.